A case of molecularly confirmed BAP1 inactivated melanocytic tumor with retention of immunohistochemical expression: A confounding factor. (23rd January 2020) - Linos, Konstantinos; Atkinson, Aaron E.; Yan, Shaofeng; Tsongalis, Gregory J.; Lefferts, Joel A.
Abstract: BRCA1‐associated Protein 1 ( BAP1 )‐inactivated melanocytic nevi/tumors (BIMT) have distinct morphologic features. A typical case exhibits a biphasic population of cytologically bland conventional melanocytes and a second proliferation of larger epithelioid melanocytes with abundant eosinophilic cytoplasm. The vast majority of cases harbor BRAF V600E in both components with bi‐allelic inactivation of BAP1 in the epithelioid component by various molecular mechanisms resulting in loss of nuclear protein expression, which can be demonstrated by immunohistochemistry. We present a case of BIMT with histopathologic features highly suggestive of this entity but unexpected retention of nuclear expression of the BAP1 protein. Subsequent molecular tests showed heterozygous loss of the BAP1 locus on the short arm of chromosome 3 (3p21.1) by chromosomal microarray analysis (CMA) and a suspected c.505C>T p.H169Y pathogenic variant identified by DNA sequencing that was subsequently confirmed by primer‐specific SNaPshot mini‐sequencing. In light of the heterozygous deletion of BAP1, this variant in the remaining allele encodes a catalytically inactive BAP1 mutant protein as shown in functional studies. The presence of a nonfunctional allele within the nucleus combined with a heterozygous deletion of BAP1 explains the clear and characteristic BIMT morphology observed by histopathology. This case underlines the potential importance of molecular diagnostics when protein expression studies do not correlate with morphology.